The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1677-55382008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen levels following transurethral resection of the prostate

Abstract: Objective: Determine how serum prostate-specific antigen (t-PSA) levels and free PSA (f/t PSA) ratio change following transurethral resection of the prostate (TURP). Results: Clinical improvement after TURP, reflected by I-PSS score, was demonstrated as early as 30 days and remained stable until the end of the follow-up. Mean t-PSA declined 71% after TURP and 60 days after surgery the reduction reached its peak, stabilizing afterwards. It varied from 6.19 ± 7.06 ng/mL before surgery to 1.75 ± 1.66 ng/mL on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Studies have shown that PSA decreases drastically in patients who undergo TURP. Fonseca et al (16), showed that mean PSA levels declined 71% after TURP, and 60 days after surgery the reduction reached its peak, stabilizing afterwards. Mean PSA varied from 6.1 ng/mL before surgery to 1.7 ng/mL after 60 days postoperatively.…”
Section: Commentsmentioning
confidence: 97%
“…Studies have shown that PSA decreases drastically in patients who undergo TURP. Fonseca et al (16), showed that mean PSA levels declined 71% after TURP, and 60 days after surgery the reduction reached its peak, stabilizing afterwards. Mean PSA varied from 6.1 ng/mL before surgery to 1.7 ng/mL after 60 days postoperatively.…”
Section: Commentsmentioning
confidence: 97%
“…It has been reported that sub-clinical hyperthyroidism is not associated with CHD or mortality from cardiovascular causes [4] but it is sufficient to induce an increase in atrial fibrillation rate [5] and increased factor X activity in patients with subclinical hyperthyroidism represents a potential hypercoagulable state [6]. It has also been reported that serum prostate-specific antigen (PSA) decreases drastically in patients who undergo transurethral resection of the prostate (TURP) [7]. We present a case of paroxysmal atrial fibrillation during acute myocardial infarction associated with subclinical hyperthyroidism, severe three vessels coronary artery disease and elevation of PSA after TURP in a 78-year-old Italian man.…”
Section: Case Reportmentioning
confidence: 99%
“…In larger prostates, it has also been shown that PSA can be reduced by 90% [ 23 ], an amount similar to that achieved with open prostatectomy. A recent study demonstrated that PSA is reduced by 71% after TURP [ 24 ]. In contrast, PSA is only reduced by 30%-42% after ablation with a potassium-titanyl-phosphate (KTP) laser [ 25 , 26 ].…”
Section: Psa Reductionmentioning
confidence: 99%